Konsentrasi Hara N, P dan Pertumbuhan Tanaman pada Tumpangsari Jagung-Kedelai yang Ditambahkan Mikoriza, Bahan Organik dan Nutrisi Tanaman di Lahan Suboptimal Lombok Utara - Astiko, Wahyu; Ernawati, NML; Silawibawa, IP (Seminar Nasional Lahan Suboptimal, 2021)
Astiko W, Ernawati NML, Silawibawa IP.Â  2021. Concentration of N, P and plant growth in maize-soybean intercropping added mycorrhizae, organic matter and plant nutrients in suboptimal land, North Lombok. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 260-268. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Suboptimal land optimization through intercropping patterns of maize and soybeans using mycorrhizal biological fertilizers and plant nutrition sources has not received much attention. This study aims to determine the concentration of P, N, and plant growth in the intercropping pattern of maize-soybean added mycorrhizal biofertilizer and plant nutrition. The experimental design used was a factorial randomized block design consisting of two treatment factors. The first factor is mycorrhizal biofertilizer (M) which consists of 2 levels: M0 = No mycorrhizal fertilizer and M1 = Using biological fertilizer (1 ton/ha). The second factor is the source of nutrition (U) which consists of 4 levels, namely: U0 = Without the addition of nutrients, U1 = With the addition of 100% dose of inorganic fertilizer only (maize = urea 300 kg/ha and Phonska 200 kg/ha, soybeans = 60 kg/ha Urea and 120 kg/ha Phonska), U2 = With the addition of 100% dose of cattle manure (12 tons/ha), and U3 = With the addition of 50% dose of cattle manure (6 t/ha) + 50% dose of inorganic fertilizer (maize = urea 150 kg/ha and Phonska 100 kg/ha, soybean = 30 kg/ha Urea and 60 kg/ha Phonska. The results showed that 50% dose of cattle manure (6 t/ha) + 50% dose of inorganic fertilizer (maize = urea 150 kg/ha and Phonska 100 kg/ha, soybean = 30 kg/ha Urea and 60 kg/ha Phonska) plus mycorrhizal biofertilizer in maize-soybean intercropping gave the best concentration of N, P and plant growth.Â